MANAGING SUBJECTIVITY AND OBJECTIVITY IN BUSINESS RESEARCH: A METHODOLOGICAL FRAMEWORK FOR INTEGRATING QUALITATIVE AND QUANTITATIVE APPROACHES - Dr.P.Vijaya Vani (The Bioscan, 2025)
Business research increasingly demands methodological pluralism. Yet the field lacks a unified framework that explicitly addresses how researchers can navigate the epistemological tension between subjective interpretation and objective measurement across the full research lifecycle. This paper proposes the Dual-Lens Integration Framework (DLIF), a structured methodology for managing subjectivity and objectivity in business research through six operationalised strategies: reflexivity auditing, systematic triangulation, structured peer debriefing, member validation protocols, bias taxonomy mapping, and transparent reporting standards. Drawing on a synthesis of empirical literature spanning policy research, education, market analysis, and healthcare, this paper argues that the qualitative–quantitative binary is a false dichotomy; rigor is achieved not by choosing one paradigm, but by consciously governing the interplay between them. Implications for managerial decision-making, strategic planning, customer experience design, and risk management are discussed. The DLIF offers both researchers and practitioners a replicable, discipline-agnostic tool for producing credible, actionable business intelligence.